Respon Dosis Pupuk NPK Pada Beberapa Varietas Terhadap Pertumbuhan Dan Produksi Kubis (Brassica Oleracea L.) - Hartanti, Aprilia; Suyani, Ida Sugeng (Agrotechbiz : Jurnal Ilmiah Pertanian, 2022)
Cabbage is a vegetable that is easily found in traditional and modern markets. Leaf vegetables belonging to the Brassicaceae family, their needs continue to increase with the increasing growth of Indonesia's population, nutritional knowledge and people's purchasing power. Generally, cabbage plants are grown in the highlands. Cabbage production has decreased which could be due to a decrease in the availability of nutrients in the soil so that the right dose of fertilizer is needed to increase production. In addition, the ability to absorb nutrients for each variety of cabbage is different. The purpose of the study of the dose of NPK fertilizer on cabbage varieties was to determine the accuracy of the dose of NPK for cabbage growth; to obtain adaptive varieties in growth and production and to determine the response of NPK doses and varieties of cabbage to the growth and production of cabbage plants. The use of RAK (Randomized Block Design) in the study with factor I was the dose of NPK (D0 = no NPK; D1 = NPK 2 grams / plant; D2 = NPK 2.25 grams / plant; D3 = NPK 2.50 grams / plant) and the second factor is the variety (V1 = Green Nova Cabbage; V2 = Green Coronet Cabbage; V3 = Grand 11 Cabbage). The conclusions of the study were that: 1. The dose of NPK fertilizer had an effect on the parameters of height, number of leaves, and wet weight of the crop 2. Types of varieties affected the parameters of plant height; 3. The dose interaction of 2 grams of NPK/plant (D1 V2) and the green coronet variety gave the best average response of root length. Keywords: NPK dose, Cabbage variety, yield